PEMBUATAN PURWARUPA ALAT PENGATUR OTOMATIS PADA TANGKI AIR MENGGUNAKAN SENSOR ULTRASONIK HC – SR04 BERBASIS PLC SR3B101BD - Santosa, Budi; Hariyadi, Hariyadi (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2019)
in the present time in the current century, almost all systems are no longer manually controlled, but automatically. The use of human labor is facilitated by tools that support almost all aspects of the work, and in this jurnal will be discussed how to create a liquid level control system automatically. Which will provide benefits for ease of doing the job. As in industry, hotels and other public facilities, which require continuous water availability to serve customers. And can be used to broaden the horizons of how a system works in real timeKeywords : tool peformance, system, automatic, control